Studi Etnobotani Masyarakat di Sekitar Kawasan Hutan Bedugul Bali - I Dewa Putu Darma; Arief Priyadi; Rajif Iryadi (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2019)
The Ethnobotany study of society advantage knowing plant species that be used and this usefulness. This study purpose identification plant’s utilization and local wisdom in Bedugul area. This method is purposive sampling that based profession with interview to Dukun, Baten, housewife, Farmer, craftsmen and builder. Filed data were processed with quantitative to get the benefit index (BI) on 181 species. Top ten species have been the highest of BI such as: Musa paradisiaca (0.026718), Arenga pinnata (0.022901), Artocarpus integer (0.015267), Cocos nucifera (0.015267), Colocasia esculenta (0.015267), Curcuma domestica (0.015267), Schizostachyum brachyckadum (0.015267), Moringa oleifera (0.01145), Aleurites moluccanus (0.01145) & Allium sativum (0.01145). Four of them have rare status i. e: Borassus flabellifer, Alstonia scholaris, Eeucresta horsfieldii & Saurauia bracteosa. Bali culture which has reserved with conservation education (Tumpek Wariga ceremony, Wana Kertih & Danau Kertih) makes the environment sustainability.